ANALYSIS OF COMPRESSIVE STRENGTH PAVING BLOCKS WITH THE ADDITION OF COCONUT FIBER AND SUPERPLASTICIZER LIQUID - Zabadi, Fairus; Taurina J. Irwanto (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2023)
This research was carried out to determine how strong the compressive strength of the Paving Block is to withstand the load above it, by adding coconut fiber and superplasticizer liquid to reduce the impact of environmental pollution. But for Paving Blocks, the effects of adding coconut fiber and superplasticizer liquid are not yet widely known. Further research needs to be done on adding coconut fiber and superplasticizer liquid in making PavingBlocks. The purpose of this research is as a form of knowledge for developing construction materials technology. This research can be used to utilize the potential of existing waste. This research aims to reduce environmental pollution caused by coconut fiber waste, and to use this waste as additional construction material technology and to find out how much compressive strength the Paving Block has so that it can be used as a construction tool. Theaddition of coconut fiber and superplasticizer liquid can improve the performance of Paving Blocks according to SNI 03-0691-1996 (compressive strength). The results from adding coconut fiber and superplasticizer liquid are higher than Normal Paving (without mixed ingredients). Paving Block 1:5 with the addition of coconut fiber and superplasticizer liquid from 5 samples produces an Average Stress fcr' of 305.42 Kg/cm and Paving Block 1:6 withthe addition of coconut fiber and superplasticizer liquid from 5 samples produces an Average Stress -Average fcr' is 237.45 Kg/cm2. Normal 1:5 Paving Block from 2 samples produces an Average Stress fcr' of 203.47 Kg/cm2and normal 1:6 Paving Block from 2 samples produces an Average Stress fcr' of 184.59 Kg/cm2 Keywords: Compressive Strength; Paving Block; Coconut Coir Fiber; Superplasticizer Liquid.